Risk Factors and Outcomes of Low Birth Weight Neonates Admitted In a Tertiary Care Center - Adhikari, Jyoti; KC, Rajesh; Kharel, Shristi (Journal of Nepalgunj Medical College, 2020)
Introduction: Birth weight